Downes score as a clinical assessment for hypoxemia in neonates with respiratory distress - Anita Rusmawati; Ekawati L. Haksari; Roni Naning (Indonesian Pediatric Society, 2008)
Background Hypoxemia in neonates with clinical respiratorydistress has a high mortality. Downes score is used as an alternativeto evaluate clinical respiratory distress if blood gas analysisinstrument or pulse oxymetry is not available.Objective To evaluate the validity of Downes score for assessinghypoxemia in neonates with clinical respiratory distress.Methods A cross sectional study was carried out on neonates withclinical respiratory distress hospitalized at level 2 and 3 NeonatalCare Unit and in Emergency Room of Dr. Sardjito GeneralHospital, Yogyakarta. Downes score and oxygen saturationmeasured by a pulse oximetry were compared. Hypoxemia wasdefined as oxygen saturation less than 90% in term and post-term infants, less than 88% in preterm neonates, or Downesscore 2:5 according to Basic Emergency Service Training forObstetry and Neonatology (PONED) in 2007. The accuracy ofDownes score in predicting hypoxemia was assessed by sensitivity,specificity, positive-predictive value, negative-predictive value,and likelihood ratio.Results Eighty nine neonates were evaluated. Downes score hadsensitivity of 88%, specificity of 81 o/o, positive-predictive value of72%, negative- predictive value of 92%, positive likelihood ratio4.53, negative likelihood ratio 0.15, prevalence of 36%, and posttest probability of 72%.Conclusion Downes score can be used as a clinical diagnosticmeans for assessing hypoxemia in clinical respiratory distressedneonates with 88% sensitivity (95% CI 79 to 99), and specificity81% sensitivity (95% CI 70 to 91).